Healthcare Workers' Perceptions of On-Site Childcare. Issue 1 (January 2023) - Braddock, Amy; Malm-Buatsi, Elizabeth; Hicks, Sarah; Harris, Grant; Alafaireet, Patricia
Abstract : Goal: Measures taken by healthcare organizations to address COVID-19 highlighted the long-standing lack of childcare infrastructure required to support healthcare workers. This study, designed to provide evidence to support operations at an academic medical center, looked at the influence that in-house and emergency childcare could have on the retention, recruitment, and productivity of healthcare workers. This study also outlined the implications that childcare, or its lack, has for healthcare organizations during and after the COVID-19 pandemic. Methods: We conducted a 35-question electronic employee survey (under institutional review board approval) during pandemic-induced public school closures, which included both quantitative and qualitative (write-in) questions. Principal Findings: The survey results showed that weekday on-site childcare was very or extremely important to more than half of survey respondents, the majority of whom were staff members (28%) or physicians (25%), followed by administrators (15%), researchers (12%), others (10%), nurses (5%), educators (2%), and residents (1%). Sixty percent of respondents reported that emergency on-site childcare was extremely important (34%) or very important (26%). Almost half (49%) reported that emergency childcare needs have disrupted their work in the past year, including canceling of clinics or surgical cases. Analysis of qualitative comments via a strategy based on coding and categorization showed that, when asked how childcare influences their work choices, employees responded that childcare availability has limited the hours or times they could work, that lack of childcare has prevented career growth, that they left a previous job or will leave their current job because of childcare needs, or that they stayed at a previous job or have remained in their current job longer because of the availability of childcare. Practical Applications: Although data from this mixed-methods study support findings in the literature that there is a need for in-house and emergency childcare, the data suggest that current employees at this academic medical center do not currently expect it, likely because such childcare is not generally available at most academic institutions. With increased rates of burnout and healthcare workers leaving the field since COVID-19, offering in-house and emergency childcare provides hospital systems with new opportunities to retain and recruit physicians, nurses, and staff, as well as to improve their well-being and productivity.